2019
DOI: 10.3168/jds.2019-17130
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin signaling and ubiquitin-proteasome–related gene expression in skeletal muscle of dairy cows with high or normal body condition score around calving

Abstract: Interpretive Summary: Mammalian target of rapamycin (mTOR) signaling and ubiquitinproteasome-(UPS) related gene expression in skeletal muscle of dairy cows with high or normal BCS around calving. By Ghaffari et al., The regulation of muscle protein turnover during a period of negative nutrient balance needs to be better understood. The objective of this study was to elucidate the effect of body condition around calving on the mRNA abundance of critical components of the mTOR pathway and UPS in the skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
4
5
0
Order By: Relevance
“…In the current study, concentrations of proteinogenic AA (except for histidine) in muscle remained fairly constant throughout the observation period despite, as reported previously (Ghaffari et al, 2019b), a concomitant decline in serum levels. The reason for these observations is not clear, but it is likely that muscle has increased transport activity to offset the decline in serum concentrations and thus maintain intracellular concentrations of the respective AA, assuming measurement at a single time point is reflective of the steady state.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, concentrations of proteinogenic AA (except for histidine) in muscle remained fairly constant throughout the observation period despite, as reported previously (Ghaffari et al, 2019b), a concomitant decline in serum levels. The reason for these observations is not clear, but it is likely that muscle has increased transport activity to offset the decline in serum concentrations and thus maintain intracellular concentrations of the respective AA, assuming measurement at a single time point is reflective of the steady state.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, as part of a physiological regulatory process, skeletal muscle that synthesizes carnosine can also release it into the circulation, probably through dipeptide transporters, to supply the needs of other tissues where it can be degraded or used (e.g., for delivery of l-histidine or β-alanine; Boldyrev, 2012). The finding that not only carnosine but also serum histidine concentrations were greater in HBCS cows on d −49 (Ghaffari et al, 2019b), may indicate 3). The pink circles show metabolites that were significantly changed and the gray circles show metabolites that were not significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in pre-and postpartum BCS and BW between the 2 groups (HBCS: prepartum 3.77 ± 0.08 and 810 ± 28 kg, postpartum 3.30 ± 0.06 and 674 ± 11 kg; NBCS: prepartum 3.16 ± 0.06 and 715 ± 25 kg, postpartum 2.89 ± 0.06 and 631 ± 12 kg) would clearly be in favor of this. Further data collected from the same study population as used herewith indicate that high BCS and BFT were associated with a greater mRNA abundance of the 2 muscle-specific ligases muscle RING finger protein-1 (MuRF-1) and atrogin-1 (Ghaffari et al, 2019), and consequently, a more stimulated proteolysis in these cows seems likely. Over-conditioned cows might then also have a greater reservoir of BCAA and counteractively a higher tissue abundance of BCAA degrading enzymes.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that cows with greater oxidative stress have a greater abundance of proteins involved in the ubiquitin proteasome pathway [27]. This pathway is responsible for removing toxins and recycling wastes from cells and tissues.…”
Section: Discussionmentioning
confidence: 99%